The Effect of Plant Growth Promoting Rhizobacteria Applications on Some Growth Parameters and Physiological Properties of Marigold (Calendula officinalis L.) Plant Grown under Drought Stress Conditions - Ezelhan ŞELEM; Lütfi NOHUTÇU; Rüveyde TUNÇTÜRK; Murat TUNÇTÜRK (Yüzüncü Yil Üniversitesi Tarim Bilimleri Dergisi, 2021)
Calendula officinalis L. species, which has an important place among medicinal plants, is used in the pharmacology, food, ornamental plant, and cosmetics industry. In recent studies, It is known that the usage areas of marigold have become increasingly widespread, but despite this widespread use, the species is quite limited of commercial production. Against drought stress, which is an important abiotic stress factor in agricultural production, BGUB (plant growth-promoting rhizobacteria) applications have come to the fore in order to minimize the decrease in yield and quality. In this study, it is aimed to determine the effects of PGPR (B0: Bacteria-free environment (control), B1; Azospirillum lipoferum, B2: Bacillus megaterium, B3: Chlorella saccharophila) applications on some growth parameters and physiological changes of C. officinalis plant grown under drought stress (normal irrigation (K1), reduced ½ (K2) ve reduced ¾ (K3)) conditions. The study was carried out in a controlled climate room with a temperature of 25oC and a humidity of 65% in a dark/light photoperiod of 8/16 hours. Seeds were sown on 28.05.2020 and were subjected to analysis of variance in randomized plot design and 3x4 factorial design. In this study, it is aimed to determine the effects of BGUKB (B0: Bacteria-free environment (control), B1; Azospirillum lipoferum, B2: Bacillus megaterium, B3: Chlorella saccharophila) applications on some growth parameters and physiological changes of C. officinalis plant grown under drought stress (normal irrigation (K1), reduced ½ (K2) ve reduced ¾ (K3)) conditions. Considering the parameters examined, drought applications were found to be statistically significant in terms of stem length (K1: 11.1 cm), root fresh (K1: 1.06 g) and dry (K1: 0.17 g) weight, stem fresh (K1: 7.26 g) weight, leaf area (K1: 7.81 cm2) and temperature (K3: 27.7 oC), epidermal cell number (K1: 593.16 number/mm2 and all stomatal characteristics. In conclusion, bacteria applications showed a significant impact on some of the characters like stem length (B1: 11.0 cm), root fresh (B1: 0.89 g) weight, stem fresh (B1: 6.09 g) weight, epidermal cell number (B1: 672.88 number mm-2), stoma length (B1: 32.71 µ) and density (B1: 11.06 number (mm2).